Analysis Of The Influence Of Organizational Climate On Productivity Of Sharia Private Banking Employees In Indonesia - Fauzie Senoaji; Akbar; Sudianto; Andi Amang; Tansri Adzlan Syah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
Islamic finance has experienced one of the greatest growth rates in the previous ten years, even outpacing traditional financial markets. The momentum created by the pandemic's end can be exploited to promote the strongest possible economic expansion. Even so, the absence of a supportive organizational climate is still felt, which naturally disturbs the climate that has already been established. Every head office employee can have opportunity to act well, perform well, and, of course, be more productive at work with a positive corporate climate. The purpose of this study is to ascertain how workplace culture affects workers' productivity. This study employs quantitative methods along with descriptive ones. A sample of 30 employees was used in this investigation. A questionnaire with four alternative answers and a Likert scale score selection form was issued to all employees as the primary method of data gathering. In the meanwhile, document analyses and interviews are merely supplementary methods of data collection. Validity and reliability tests are used to assess the instruments employed, and then overall valid and reliable data is created. Data processing procedures are used to test the data's overall quality. The correlation between organizational climate and productivity was found to be 36%, and this finding indicates that organizational climate influences 36% of productivity, with the other 36% influenced by factors not included in this study.